Nutritional Status and Dietary Intake of School-Age Children and Early Adolescents: Systematic Review in a Developing Country and Lessons for the Global Perspective - Khan, Durray Shahwar A.; Das, Jai K.; Zareen, Shagufta; Lassi, Zohra S.; Salman, Afsah; Raashid, Muhammad; Dero, Aftab A.; Khanzada, Aijaz; Bhutta, Zulfiqar A. (Frontiers in Nutrition, 2022)
Background: The prevalence of double burden of malnutrition (DBM) is high in low- and middle-income countries (LMICs). Data on malnutrition trends is present for children less than five years of age, however the data for school-going children and adolescents aged 5 to 15 years is scarce. Objective: This systematic review presents the pooled prevalence of nutritional status and dietary intake among school-going children and adolescents (5 to 15 years of age) in an LMIC of Pakistan and the perspective for broader global nutrition in this age group. Methods: An electronic search of databases was run on Pubmed and Medline (via Ovid) along with grey literature and archives of local scientific journals till 2nd January 2021. Studies meeting the eligibility criteria were included and relevant data were extracted, and a pooled proportional analysis was performed. Results: A total of 51 studies including 62,148 children of 5-15 years met the inclusion criteria, of which 30 studies reported on anthropometric indices alone, eight on dietary intake patterns while 13 reported both. All of the included studies had a cross-sectional study design. There were 20 studies from the province of Punjab, 15 from Sindh, eight from Khyber Pakhtoonkhwa, two from Balochistan, and three from multiple cities across Pakistan. The pooled proportional analysis showed that the proportion of underweight children and adolescents was 25.1% (95% CI 17.3% to 33.7%); stunting 23% (95% CI 11.8% to 36.7%); wasting 24% (95% CI 15.2% to 34%); thinness 12.5% (95% CI 9.4% to 16.1%); overweight 11.4% (95% CI 7.2% to 16.3%); and obesity 6.9% (95% CI 3% to 12%). A relatively high intake of carbohydrates, soft drinks, and sweets/chocolates; and a low intake of protein-rich foods, fruits, and vegetables was reported. Conclusion: The limited data suggests the presence of DBM amongst children aged 5 to 15 years and also identified that dietary intake patterns are not meeting the recommended allowance. This review highlights the gaps and the need for larger, well-designed studies for this age group with the representation of different contexts and the need for similar studies in various LMICs, so that appropriate actions be deliberated.